Creama : uma arquitetura de referência para o desenvolvimento de sistemas colaborativos móveis baseados em componentes - Melotti, Maison (2014)
Collaborative systems are systems that support two or more users engaged in a common task, providing an interface to a shared environment for these users and mobile applications have become an important part of the collaboration support tools. When used in the context of mobility, collaborative systems can be called mobile collaborative systems. These systems allow, for example, that cooperate teams while in motion, increasing the potential of collaboration. Tools to support software developers are very important in general, but with regard to mobile collaboration tools become paramount, especially because it is a multidisciplinary field that deals with many technical issues. However, without a foundation of requirements or models that map these requirements to support, often the tooling may become unusable or less useful. Therefore, it is very important to provide support to the development of mobile collaborative systems through a set of tools and methods to support the developer in creating these systems. Because of this, in this work was developed CReAMA, a reference architecture to guide the development of component-based mobile collaborative systems. In the reference architecture definition was also performed a CReAMA evaluation in order to comply with a comprehensive view the validity of the proposal.